IMPACTS OF DESIGN THINKING COURSE FOR UNDERGRADUATE STUDENTS IN A PRIVATE HIGHER EDUCATION INSTITUTION - Menaga Vesudevan; Intan Syafinaz Mohd Rozee; Wan Noor Farah Wan Shamsuddin; Lim Chia Wei (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The general idea behind any Design Thinking course is to expand the creativity and critical thought process of students in their studies and develop these highly sought after skillsets at the tertiary level. In this study, the Design Thinking course helps students to develop practical and innovative solutions based on the problems that figured and need to have a solution. This research explores the impacts of the Design Thinking course for undergraduate students in a private institution in Negeri Sembilan, Malaysia. This research was conducted with the use of a quantitative research method through an online survey and was distributed to 114 students at the end of the course. This was done to examine the impacts of the Design Thinking course. Furthermore, the survey questionnaire was used as the main tool for data collection. The findings show a positive impact of the Design Thinking course for undergraduate students, the course has given a great platform to students and having a design thinking mindset to think more creatively.